2015
DOI: 10.1107/s1600576715012832
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and mechanisms of cemented carbides with ultrahigh fracture strength

Abstract: WC-Co cemented carbides were prepared by liquid-state sintering of in situ synthesized composite powders with a constant Co content but different carbon concentrations, and with different size scales of VC particles as grain-growth inhibitor. With an optimized carbon addition and doping with microscale VC particles, an ultrahigh fracture strength with a mean value above 5000 MPa was achieved for cemented carbides. By detailed crystallographic analysis of the configuration and interactions of the WC, Co and VC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
(32 reference statements)
0
16
1
Order By: Relevance
“…However, as the volume fraction of the metal binder in the cemented carbides is much smaller than that of WC, the plastic accommodation from the binder is strongly restricted by the contiguity of WC grains. Thus, improving the toughness of the hard carbide matrix may effectively enhance the resistance against the transgranular fracture of the cemented carbide (Liu et al, 2015). In this respect, experiments and molecular dynamics simulations based on nanoindentation and uniaxial compression have been performed to examine the deformation characteristics of WC (Fang et al, 2019;Bl'anda et al, 2014;Csaná di et al, 2015;Tarragó et al, 2016;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the volume fraction of the metal binder in the cemented carbides is much smaller than that of WC, the plastic accommodation from the binder is strongly restricted by the contiguity of WC grains. Thus, improving the toughness of the hard carbide matrix may effectively enhance the resistance against the transgranular fracture of the cemented carbide (Liu et al, 2015). In this respect, experiments and molecular dynamics simulations based on nanoindentation and uniaxial compression have been performed to examine the deformation characteristics of WC (Fang et al, 2019;Bl'anda et al, 2014;Csaná di et al, 2015;Tarragó et al, 2016;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that the plasticity and toughness of the cermets are determined by the binder metal due to its intrinsic mechanical features (García et al, 2018). However, in our previous work, we found that the carbide matrix is also resistant to transgranular fracture through its deformation behavior (Liu et al, 2015). Therefore, to distinguish the contributions of carbide matrix and binder to the plasticity of cermets is of great importance (Fischmeister et al, 1988;.…”
Section: Introductionmentioning
confidence: 88%
“…As a class of intrinsically brittle materials, the fracture toughness of cemented carbides is generally considered as the bottleneck of its mechanical properties. Thus, the improvement of fracture toughness while controlling the decrease in hardness and hence the enhancement of the fracture strength of cemented carbides is very challenging, especially as grain size decreases to the nanoscale (Cha et al, 2001;Liu et al, 2012Liu et al, , 2015. For nanocrystalline cemented carbides, due to the decrease of WC grain size, an ultrahigh hardness can be obtained.…”
Section: Introductionmentioning
confidence: 99%